Immunodynamic axis of fibroblast-driven neutrophil infiltration in acute pancreatitis: NF-κB–HIF-1α–CXCL1 - Qiang Wang; Xiao Zhang; Chenglong Han; Zhenyi Lv; Yi Zheng; Xuxu Liu; Zhiwei Du; Tianming Liu; Dongbo Xue; Tao Li; Liyi Wang (Cellular & Molecular Biology Letters)
Abstract Background Acute pancreatitis (AP) is a sterile inflammation, and 10–20% of cases can progress to severe acute pancreatitis (SAP), which seriously threatens human life and health. Neutrophils and their extracellular traps (NETs) play an important role in the progression of AP. However, the immunodynamic factors between the excessive infiltration of neutrophils during the occurrence of AP have not been fully elucidated. Methods Adult male C57BL/6 J mice were selected. An AP model was induced by cerulein, and a control group was set up. Single-cell sequencing technology was used to reveal the cell atlas of AP pancreatitis tissue. In vivo, the model mice were treated with anti-Ly6G antibody, DNase I, SC75741, PX-478, and SRT3109 respectively. In vitro, human pancreatic stellate cells were treated with hypoxia, H2O2, NAC, and JSH-2, and co-cultured with neutrophils in Transwell chambers. The severity of inflammation was evaluated, and the molecular mechanism by which fibroblasts exacerbate AP was revealed through techniques such as cell colony formation assay, cell migration assay, cell transfection, immunofluorescence, flow cytometry, Western blot, reverse-transcription quantitative polymerase chain reaction (RT-qPCR), and co-immunoprecipitation (co-IP). Results The study showed that the elimination of neutrophils and NETs could significantly improve AP. Single-cell RNA sequencing (scRNA-seq) indicated that both neutrophils and fibroblasts in pancreatic tissue exhibited heterogeneity during AP. Among them, neutrophils highly expressed CXCR2, and fibroblasts highly expressed CXCL1. Further experimental results demonstrated that the infiltration of neutrophils in the early stage of AP was related to the activation of fibroblasts. The activation of fibroblasts depended on the nuclear factor kappa B (NF-κB) signaling pathway induced by hypoxia. NF-κB enhanced the activation of pancreatic stellate cells (PSCs) and the secretion of CXCL1 by directly promoting the transcription of HIF-1α and indirectly inhibiting PHD2, resulting in the accumulation of HIF-1α protein. The NF-κB–HIF-1α signal promoted the secretion of CXCL1 by fibroblasts through glycolysis and induced the infiltration of neutrophils. Finally, blocking the NF-κB–HIF-1α–CXCL1 signaling axis in vivo reduced the infiltration of neutrophils and improved AP. Conclusions This study, for the first time, demonstrated that activation of fibroblasts is one of the immunological driving factors for neutrophil infiltration and elucidated that glycolysis driven by the NF-κB–HIF-1α pathway is the intrinsic molecular mechanism by which fibroblasts secrete CXCL1 to chemotactically attract neutrophils. This finding provides a highly promising target for the treatment of AP.